1996
DOI: 10.1002/1529-0131(199604)9:2<82::aid-anr1790090203>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

A survey of exercise beliefs and exercise habits among people with arthritis

Abstract: Objective. To explore a possible explanation for the problem of why few people exercise despite the positive health advantages, by examining the relationship between exercise beliefs and participation in exercise activities. Methods. Eighty‐one respondents aged 27–80 were recruited from 3 Chicago‐area health care facilities to complete the study survey; 68 (84%) did so. Participants were asked about their participation in 6 types of exercise activities; they also reported their beliefs concerning their ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(87 citation statements)
references
References 17 publications
4
81
2
Order By: Relevance
“…Supporting the findings from this study, Gecht et al (14) explored the exercise beliefs among people with arthritis and found that individuals were most likely to exercise if they believed in the benefits of exercise (14). In addition, in a longitudinal interview study nested within a randomized controlled trial of exercise for older adults with knee pain, Hurley et al (16) found that older adults with knee problems commonly attributed their pain to wear and tear or arthritis, believed that no cure was available, and expressed concerns over the safety of exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting the findings from this study, Gecht et al (14) explored the exercise beliefs among people with arthritis and found that individuals were most likely to exercise if they believed in the benefits of exercise (14). In addition, in a longitudinal interview study nested within a randomized controlled trial of exercise for older adults with knee pain, Hurley et al (16) found that older adults with knee problems commonly attributed their pain to wear and tear or arthritis, believed that no cure was available, and expressed concerns over the safety of exercise.…”
Section: Discussionmentioning
confidence: 99%
“…The central role that attitudes and beliefs play in determining health-related behavior, including exercise, is highlighted in many social cognitive models (summarized by Horne and Weinman [13]), and existing evidence supports the link between the attitudes and beliefs of older adults with knee pain and their exercise and physical activity behavior (14,15). Some qualitative studies have already suggested that individuals may hold unhelpful attitudes and beliefs about their knee problems and about the role of exercise in managing their pain, which could be a barrier to exercise and physical activity behavior (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…The Exercise Beliefs Questionnaire, an instrument developed by Gecht et al (38) for patients with arthritis (replaced herein with FM), includes 20 items that address self efficacy for exercise, barriers to exercise, benefits of exercise, and impact of exercise on FM. This measure was administered to all 726 Dobkin et al subjects at baseline, posttreatment, and 3 months posttreatment.…”
Section: Exercise In Women With Fibromyalgiamentioning
confidence: 99%
“…In comparison, adherence rates to medical regimens range from 16% to 84% (11). Reported determinants of adherence to short-term exercise regimens in patients with RA are self efficacy, previous exercise habits, attitude towards the exercise program, and (perceived) severity of the disease (12)(13)(14)(15)(16). Data regarding adherence or determinants of adherence to long-term exercise programs in RA are sparse.…”
Section: Introductionmentioning
confidence: 99%